Perceived usefulness as a correlate of extent of information and communications technologies (ICTs) use for teaching by library educators in universities in Nigeria (2017)
Information and Communications Technologies(ICTs) integration for teaching is the application of information, communication and telecommunication technologies, equipment and hardware for instructional purposes. With ICT, a lot of information resources and software can be provided on time and with ease. The research presumed that the perception of how useful for teaching (or otherwise) the ICTs are may affect their use among library educators in Nigerian universities. To establish or refute this, descriptive survey design was adopted and the population is 293 educators engaged in 27 universities. All the educators participated in the study. Out of the 293 copies of the questionnaire distributed, 211 copies were returned of which only 208 copies were found useful giving a response rate of 72%. The scales: Extent of Use (r = 0.883) and perceived usefulness (r = 0.959) were used to collect data which was analysed using descriptive and inferential statistics to answer two research questions and test an hypothesis at 0.05 level of significance. Perceived usefulness was found to be negative. Analysis of its influence on the extent of use of ICT for teaching showed significant correlation(r = 0.174; p>0.05). This implies that the library educators perceived ICT not useful for teaching LIS courses and that the extent they will go in using ICT was dependent on how useful they perceived ICT. This may explain the low use of ICT for teaching among them. Therefore, training and support programmes should be designed to encourage a positive perception and an increase use of a wider range of ICTs for quality and effective teaching practices.